G-QUADRUPLEX LIGANDS AS STABILIZER TARGETING TELOMERASE ENZYME AS ANTI CANCER AGENTS - Cn, Hemalatha; M, Vijey Aanandhi; M, Vijey Aanandhi (Asian Journal of Pharmaceutical and Clinical Research, 2017)
The human telomere stabilization with G-Quadruplex DNA tends to induce apoptosis. The molecular target of telomere cascade with a rigid molecular may show efficacious to treat cancer. The study of intercalation to human telomeric DNA with proposed ligand can be evaluated by the help of biophysical studies and biological studies. G-Quadruplex is one of the key epigenetic episodes of eukaryotes and prokaryotes, generally found in the telomeric end region, immunoglobulin switch recombination and the lagging strand of the DNA. These chemotherapeutic advances are not enough to maintain a life expectancy of cancer affected patients. A number of G-Quadruplex ligands such as acridine, perylene, and anthraquinones have been synthesized reported and evaluated them for the inhibitor activity. Therefore, translational research can pave the novel prospect to treat cancer in a fundamental way. In that connection, basic research showed G-Quadruplex phenomenon of DNA, which is having a great impact in this chemotherapy.